2010
DOI: 10.5713/ajas.2010.10025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chito-oligosaccharide Supplementation on Egg Production, Nutrient Digestibility, Egg Quality and Blood Profiles in Laying Hens

Abstract: This study was conducted to evaluate the effects of dietary supplementation with chito-oligosccharide (COS) on egg production, nutrient digestibility, egg quality and blood profiles in laying hens. A total of 240 Hy-line Brown laying hens were randomly allocated into one of the following 5 dietary treatments: i) CON, basal diet; ii) ANT, basal diet+44 mg/kg avilamycin; iii) COS0.2, basal diet+200 mg/kg COS; iv) COS0.4, basal diet+400 mg/kg COS; v) ANTCOS, basal diet+200 mg/kg COS+22 mg/kg avilamycin. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 17 publications
6
32
0
Order By: Relevance
“…Similar results were found in a study by Meng et al (2010) who reported that dietry COS0.2 and COS0.4 did not improve the egg weight in 28-wk-old laying hens. Nogueira et al (2003) reported that addition of chitosan (20 g/kg) had no effect on the egg weight, contrarily, the addition of chitosan (30 g/kg) had lower egg weight compared to the basic diet and chitosan (20 g/kg) supplemented diet in 14-wk-old laying hens.…”
Section: Egg Qualitysupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were found in a study by Meng et al (2010) who reported that dietry COS0.2 and COS0.4 did not improve the egg weight in 28-wk-old laying hens. Nogueira et al (2003) reported that addition of chitosan (20 g/kg) had no effect on the egg weight, contrarily, the addition of chitosan (30 g/kg) had lower egg weight compared to the basic diet and chitosan (20 g/kg) supplemented diet in 14-wk-old laying hens.…”
Section: Egg Qualitysupporting
confidence: 90%
“…Yan et al (2010) also reported that dietary inclusion of COS (0.01% and 0.02%) had a linear increase in egg yolk color and HU was prominent. Meng et al (2010) found that the birds in the COS0.2, COS0.4 groups had higher (P<0.05) HU than those fed CON diet at the end of the week 6. These results indicate that the effects of COS may have the positive effect on HU of the egg.…”
Section: Egg Qualitymentioning
confidence: 84%
See 1 more Smart Citation
“…Meng et al. () observed increased WBC and blood total protein concentration in blood of layers fed diet supplemented with COS (0.02 and 0.04%).…”
Section: Haematological and Biochemical Blood Characteristics And Lipmentioning
confidence: 99%
“…The goal of a study by Meng et al. () was to evaluate the effects of diet supplementation with COS (0.02% or 0.04%) on egg production and quality and nutrient digestibility in Hy‐Line Brown layers. The results showed that both supplementation levels of COS had a positive influence on laying intensity, egg quality as measured in Haugh units and apparent digestibility of dry matter and nitrogen.…”
Section: Performance and Digestibility Measurementsmentioning
confidence: 99%